Pengembangan Model Sistem Informasi Penerimaan Peserta Didik Baru Untuk Sekolah Pendidikan Anak Usia Dini - Faizal, Fritzen; Noprisson, Handrie (JSAI (Journal Scientific and Applied Informatics), 2024)
The purpose of this study is to change the registration system from the original manual with a registration form to a web-based new student admission information system (PPDB) that is in accordance with the needs of the school with data collection methods and waterfall models. The research stages on the development of a Web-based new student admission information system (PPDB) at El-Fash Islamic Kindergarten include the stages of analyzing user and functional needs of the system, system design, implementation and testing. This research was conducted focusing on the problem of New Student Admission (PPDB) at El-Fash Islamic Kindergarten (TK) Jurang Manggu Timur, Pondok Aren District, South Tangerang City. The research was conducted in the period June 2023 to June 2024. As a result of the research, this system supports users (parents/guardians) to fill out the registration form, print the completed registration form into *.pdf form, view the registration results, send proof of payment of the total registration fee. In addition, administrators can add, edit, delete PPDB pages, registrant data, payment data, registration fees, and entry fee details, make PPDB results announcements and manage users by granting appropriate access rights, such as school admins or users (parents/guardians).